Evaluating Education in Greenland: How is Power Exercised through Evaluation Models? - Boolsen, Merete Watt (Scandinavian Journal of Public Administration, 2012)
Education plays an unquestionable role in society. Various sociological models of what education does, how it works and the problems involved explain why it constitutes a battleground for potential social and political conflict. How education is measured or evaluated is equally conflict material. In the present article, traditional evaluation models are applied in a somewhat atypical context: Greenland. Here, the government launched an ambitious education reform in 2005 aimed at increasing both the level and quality of education. The results of the evaluations have been ‘disappointing’ thus far – the reform has failed. The article begins by presenting different evaluation models applied in the Greenlandic context (program and summative evaluations). Second, a discussion of findings covering the initial period 2005‒10. Finally, a change in evaluation strategy is suggested with Michael Quinn Patton’s developmental evaluation model. Is it fair, relevant or constructive to examine education in Greenlandic society through the evaluation lens from a European society?